Tradition, Meaning and Training in the Development of Female Bricklayers in Latin America - Montes-Ponce, Wendy Margarita (Corporación Universitaria del Caribe, CECAR., 2020)
The participation of Female Bricklayers in construction has increased in recent years. Training in the trade represents disadvantages that originate, both biologically and gender. The purpose of this article is to expose the conditions under which Female Bricklayers develop in Latin America, demonstrating that labor recognition has undergone political, business and social assemblies, until achieving their formalization of academic learning, enhancing their knowledge, skills and family economy. Progress has paid off positively. However, permanent public policies are required to strengthen academic programs, involving urban and rural environments.